Acute myocardial infarction incidence and survival in Aboriginal and non-Aboriginal populations: an observational study in the Northern Territory of Australia, 1992–2014. Issue 10 (8th October 2020) - Coffey, Cushla; Zhao, Yuejen; Condon, John R; Li, Shu; Guthridge, Steven
Abstract : Objectives: To examine long-term trends in acute myocardial infarction (AMI) incidence and survival among Aboriginal and non-Aboriginal people. Design: Retrospective cohort study. Setting, participants: All first AMI hospital cases and deaths due to ischaemic heart disease in the Northern Territory of Australia (NT), 1992–2014. Main outcome measures: Age standardised incidence, survival and mortality. Results: The upward trend in Aboriginal AMI incidence plateaued around 2007 for males and 2001 for females. AMI incidence decreased for non-Aboriginal population, consistent with the national trends. AMI incidence was higher and survival lower for males, for Aboriginal people and in older age groups. In 2014, the age standardised incidence was 881 and 579 per 100 000 for Aboriginal males and females, respectively, compared with 290 and 187 per 100 000 for non-Aboriginal counterparts. The incidence disparity between Aboriginal and non-Aboriginal population was much greater in younger than older age groups. Survival after an AMI improved over time, and more so for Aboriginal than non-Aboriginal patients, because of a decrease in prehospital deaths and improved survival of hospitalised cases. Conclusions: There was an important breakpoint in increasing trends of Aboriginal AMI incidence between 2001 and 2007. The disparity in AMI survival between the NT Aboriginal and non-Aboriginal populations reduced over time as survival improved for both populations.